Qualidade de sementes de algodoeiro (Gossypium spp.) submetidas ao controle biológico. - Farias, Otília Ricardo de (2017)
The occurrence of phytopathogenic fungi in cotton seeds can result in significant production losses. The objective was to determine the health and physiological quality and the effect of biological products based on Trichoderma spp. and Bacillus spp. in the treatment of cotton seeds in the control of Fusarium oxysporum f. sp. vasinfectum. In the evaluation of the sanitary and physiological quality, 10 lots of cotton seeds were used. The method used to detect fungi in the seeds was the filter paper (blotter test). To evaluate the physiological quality of the seeds, a germination test was performed, which counted normal seedlings, abnormal and with primary infection, dead and hard seeds, first count and germination speed index, length and dry matter of seedlings. To evaluate the effect of biological products based on Trichoderma spp. and Bacillus spp., mocó cotton seeds (Casserengue) from cv BRS 286 and Topázio were submitted to the following treatments: T1 - Control (without treatment); T2 - Trichodel® (0.5 mL); T3 - Trichodel® (1.0 mL); T4 - Trichodel® (1.5 mL); T5 - Trichodel® (2.0 mL); T6 - Bactel® (2.0 mL); T7 - Bactel® (2.5 mL); T8 - Bactel® (3.0 mL); T9 - Bactel® (3.5 mL) diluted in 100 mL of ADE; T10 - Captana fungicide. To evaluate the behavior of Fov inoculated in seeds treated with biological products, its incidence in cotton seeds and the physiological quality of the treated seeds. The Fov inoculation methods were: 1) inoculation of the substrate with conidia suspension; 2) immersion of the seeds in the suspension of conidia and 3) direct contact of the seeds with mycelium of the pathogen. The percentage of seedlings with vascular darkening, shoot length and disease severity was evaluated. 23 genera of fungi were identified in cotton seeds, being Fusarium sp., Cladosporium sp., Penicillium sp. and Colletotrichum sp. the most frequent. A reduction in the physiological quality of the seeds was observed due to the fungal infection. The biological product Trichodel® reduces the incidence and severity of Fov in cotton seedlings and does not affect the physiological quality of the treated seeds.